Hybrid perovskite quantum nanostructures synthesized by electrospray antisolvent-solvent extraction and intercalation - Naphade, Rounak; Nagane, Satyawan; Shanker, G. Shiva; Fernandes, Rohan; Kothari, Dushyant; Zhou, Yuanyuan; Padture, Nitin P.; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2016)
Perovskites based on organometal lead halides have attracted great deal of scientific attention recently in the context of solar cells and optoelectronic devices due to their unique and tunable electronic and optical properties. Herein, we show that the use of electrospray technique in conjunction with the antisolventsolvent extraction leads to novel low-dimensional quantum structures (especially 2-D nanosheets) of CH3NH3PbI3- and CH3NH3PbBr3-based layered perovskites with unusual luminescence properties. We also show that the optical bandgaps and emission characteristics of these colloidal nanomaterials can be tuned over a broad range of visible spectral region by compositional tailoring of mixed-halide (I- and Br-based) perovskites.
Keywords: 2D nanostructure systems; antisolvent-solvent extraction; bandgap tuning; electrospray; nanosheets; perovskite; quantum dots

Hexaphosphate-derived phosphorus-functionalized carbon for lithium-ion battery anode - Gawli, Yogesh; Wahid, Malik; Fernandez, Rohan; Kothari, Dushyant; Shelke, Manjusha; Ogale, Satishchandra B. (Chemistryselect, 2017)
We show that high-temperature annealing of a dried hexaphosphate, namely phytic acid, renders activated (micro-porous) and phosphorus-functionalized graphene like carbon in a one-step process. At high enough temperature few volatile phosphates serve as porogen-forming entities while other groups reactively functionalize the carbon surface. The optimized material has high effective surface area due to the presence of defect states. As an anode material for Li-ion battery, it exhibits a reversible capacity that is double that of the graphite and is stable for 1000 cycles even at a high current of 5 A g(-1). This result is attributed to the concurrent presence of micropores and phosphorus containing groups in the carbon matrix.